Chromosome Segregation Defects Contribute to Aneuploidy in Normal Neural Progenitor Cells - Yang, Amy H. (J Neurosci, 2003)
Recent studies based predominantly on nucleotide hybridization techniques have identified aneuploid neurons and glia in the normal brain. To substantiate these findings and address how neural aneuploidy arises, we examined individual neural progenitor cells (NPCs) undergoing mitosis. Here we report the identification of chromosomal segregation defects in normal NPCs of the mouse cerebral cortex. Immunofluorescence in fixed tissue sections revealed the presence of supernumerary centrosomes and lagging chromosomes among mitotic NPCs. The extent of aneuploidy followed the prevalence of supernumerary centrosomes within distinct cell populations. Real-time imaging of live NPCs revealed lagging chromosomes and multipolar divisions. NPCs undergoing nondisjunction were also observed, along with interphase cells that harbored micronuclei or multiple nuclei, consistent with unbalanced nuclear division. These data independently confirm the presence of aneuploid NPCs and demonstrate the occurrence of mitotic segregation defects in normal cells that can mechanistically account for aneuploidy in the CNS.